Adam Habib’s Rebels and Rage. Reflecting on #FeesMustFall: A critical appraisal - Blackmur, D.J. (South African Journal of Higher Education, 2019)
ABSTRACT This article offers a critical review of the analysis, arguments and some of the conclusions in Adam Habib’s recent book Rebels and Rage: Reflecting on #FeesMustFall (Habib 2019). The article is necessarily selective about events and issues: others might offer different, and welcome, perspectives. This article thus cannot provide a substitute for a careful reading of Habib’s provocative, sometimes irritating, sometimes insightful, but nevertheless important book. The importance of the book lies principally in the questions it stimulates about the nature and the future of the South African university.